Optimasi Adsorpsi Ion Fe3+ Menggunakan Adsorben Silika Gel Sulfonat - Chindikia, Ilmy; Oktavia, Budhi; Putra, Ananda; Nasra, Edi (Departemen Kimia FMIPA UNP, 2024)
Adsorption is a process of absorption of adsorbate or substances absorbed by the surface of the adsorbent or absorbent substance which aims to reduce the Fe3+ cation in a solution. Research has been carried out on the adsorption of Fe3+ cations using silica sulfonate adsorbents by varying the pH and contact time to obtain optimum conditions during adsorptions. The adsorption process of Fe3+ cations used a sulfonate modified silica gel adsorbent has been carried out by varying the pH, namely 2; 3; 4; 5; 6; 7 and the maximum pH has been fixed at pH 6 with an abdorption capacity of 2,32732 mg/g with an absorpyion percentage of 78.79 %, contact time variations of 15; 30; 45; 60; 75 minutes have been obtained for optimum contact time at 45 minutes with an absorption capacity of 2,225756 mg/g and absorption percent of 77,33 %